Elite Canadian women rugby athletes` attitude to and experience of physical aggression - Kerr, J. (The Sport Psychologist, 2018)
Elite Canadian women rugby union athletes' (N = 10) attitude to and experience of physical aggression was investigated in this study. The methodology adopted in this post-positivist study was a deductive qualitative approach and involved theoretical thematic data analysis. The analysis and interpretation of data was informed by Kerr's (2005) distinction between sanctioned and unsanctioned forms of aggression. Open-ended, semi-structured interviews provided ample evidence that rugby provided pleasurable experiences through active physicality and sanctioned play aggression. With regard to unsanctioned aggression, backs and forwards recounted incidents of unsanctioned aggression perpetrated against them by opponents. Backs' interview statements indicated no real involvement in unsanctioned aggression, but the majority of forwards had perpetrated acts of anger and power unsanctioned aggression against opponents. No incidents of thrill-based unsanctioned aggression were described by the elite women athletes. Suggestions for future aggression research are discussed.